Pengaruh Keteladanan Orang Tua Dalam Pembentukan Perilaku Anak Usia Dini - Juwita, Tita; Yunitasari, Septiyani Endang (Jurnal Ilmiah Wahana Pendidikan, 2024)
The increase in acts of violence and crime in society, one of the influencing factors is a moral crisis or weak character strengthening. A child's golden age is the time when a child's behavior is formed. Children are more likely to follow what they see compared to what they hear. This means that children tend to imitate and not just follow orders. If parents show exemplary behavior, in the form of honesty, trustworthiness, noble character, courage and staying away from actions that are contrary to religion. This research aims to obtain an overview of the impact of the absence of role models on parents which will result in children easily imitating deviant behavior which then forms behavior that becomes character. The method used in this research is descriptive qualitative. Data collection techniques use interview, observation and documentation techniques. The data collected was analyzed through a reduction process, data presentation and drawing conclusions. The results of the research show that the formation of bad behavior in early childhood has an effect on the subsequent growth period so that later it can turn into someone who experiences a moral crisis. The increasing moral crisis or moral degradation in society will result in an increase in crime, so the role of parents is very important in creating quality human resources. This research aims to obtain an overview of the impact of the absence of role models on parents which will result in children easily imitating deviant behavior which then forms behavior that becomes character. The method used in this research is descriptive qualitative. Data collection techniques use interview, observation and documentation techniques. The data collected was analyzed through a reduction process, data presentation and drawing conclusions. The results of the research show that the formation of bad behavior in early childhood has an effect on the subsequent growth period so that later it can turn into someone who experiences a moral crisis. The increasing moral crisis or moral degradation in society will result in an increase in crime, so the role of parents is very important in creating quality human resources.